Ankle Pump Exercise as Evidence-Based Nursing for Managing Hypervolemia in Chronic Kidney Disease Patients - Zulfiana Nurlaili; Nur Asa Rhahmadani Susanti; Beti Kristinawati; Afif Riada Pratama (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypervolemia in patients with Chronic Kidney Disease (CKD) can cause lower extremity oedema. Non-pharmacological methods like ankle pump exercises and 30° leg elevation effectively reduce oedema and improve circulation by utilising muscle pump action and gravity to enhance venous return to the heart. The purpose of this case report evaluates the patient's response to the therapy provided. The method used is a descriptive design informed by evidence-based nursing (EBN). Data collection was conducted through interviews, observations, and the review of secondary data from medical records. The degree of oedema was measured using the Brodovicz pitting oedema scale. The study subject was Mrs S, a 60-year-old woman with stage V chronic kidney disease (CKD). She experienced fluid overload, shown by swelling, high neck vein pressure, weight gain, and low urine output. The intervention was carried out during four sessions, each lasting 40 minutes. The evaluation included the degree of oedema (Brodovicz pitting oedema), weight change, and foot circumference measurement. The results showed a decrease in the degree of oedema from 3 to 2, a decrease in weight from 48 kg to 46 kg, and an increase in urine output. Patients reported a reduction in heaviness and swelling in the lower extremities after the Ankle Pump Exercise and 30° leg elevation interventions, and no side effects were found during the implementation of these two interventions. Ankle pump exercise and 30° leg elevation proved to be effective, safe, and easy to apply as part of self-care. The results indicate that ankle pump exercise and 30° leg elevation can be used as non-pharmacological nursing interventions in the management of oedema in CKD patients with hypervolemia. Nurses play a crucial role in educating and guiding patients and their families to help them perform self-care interventions independently and continuously.